1998
DOI: 10.1016/s0886-3350(98)80223-x
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser phototherapeutic keratectomy for recurrent pterygium

Abstract: Excimer laser PTK appears to simplify pterygium surgery because a superficial keratectomy is sufficient to remove pterygium. The excimer laser can be used to ablate the visible residual tissues and smooth the corneal surface, resulting in good postoperative refraction and visual acuity. Consequently, this procedure seems to be effective and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…They reported a recurrence rate of 91% while 3 years later, Förster et al [30,31] reported about 33-57% in two series of 50 and 46 eyes. Talu et al [32] reported a 4.5% recurrence rate, while Walkow et al [33] observed a significantly reduced astigmatism in a series of 60 eyes that had undergone bare-sclera resection combined with excimer smoothing. They also suggested the postoperative use of locally applied mitomycin C, which they report yielded a recurrence rate of 5% [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…They reported a recurrence rate of 91% while 3 years later, Förster et al [30,31] reported about 33-57% in two series of 50 and 46 eyes. Talu et al [32] reported a 4.5% recurrence rate, while Walkow et al [33] observed a significantly reduced astigmatism in a series of 60 eyes that had undergone bare-sclera resection combined with excimer smoothing. They also suggested the postoperative use of locally applied mitomycin C, which they report yielded a recurrence rate of 5% [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The use of more sophisticated conjunctival surgery is associated with considerably lower recurrence rates, often less than 10% (16,78). Other modalities for pterygium removal, such as ablation with excimer laser, have not gained widespread acceptance, although excimer laser may have a role in smoothening corneal surface irregularities caused by pterygium (81,82). However, lamellar karatoplasty may also be required, especially in cases of recurrent pterygia with firm adhesion to the corneal stroma (83).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Over the past few decades, several surgical methods for pterygium have emerged, ranging from the bare sclera procedure without microscopy to very complex approaches such as amniotic membrane transplantation and lamellar keratoplasty [1, 2]. Some adjunct therapies also are used such as beta-radiation, excimer laser and antimetabolites to lower the recurrence rates, but these may sometimes be associated with severe complications [3,4,5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%